2015
DOI: 10.1186/s12863-015-0187-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL underlying physiological and morphological traits of flag leaf in barley

Abstract: BackgroundPhysiological and morphological traits of flag leaf play important roles in determining crop grain yield and biomass. In order to understand genetic basis controlling physiological and morphological traits of flag leaf, a double haploid (DH) population derived from the cross of Huaai 11 × Huadamai 6 was used to detect quantitative trait locus (QTL) underlying 7 physiological and 3 morphological traits at the pre-filling stage in year 2012 and 2013.ResultsTotal of 38 QTLs distributed on chromosome 1H,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 54 publications
6
54
1
Order By: Relevance
“…Under rainfed conditions, the crop must increase water use efficiency to resist drought, and sustains normal growth (Liu, Sun, Ren, Li, & Sun, 2015). The relative water content (RWC) has been widely used to measure the water status in barley, and various QTLs for RWC on chromosomes 2H, 4H, 5H, 6H and 7H have been detected in different water conditions (Teulat et al, 2003;Fan, Shabala, Ma, Xu, & Zhou, 2015;Liu et al, 2015). In the current study, no QTLs controlling RWC were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Under rainfed conditions, the crop must increase water use efficiency to resist drought, and sustains normal growth (Liu, Sun, Ren, Li, & Sun, 2015). The relative water content (RWC) has been widely used to measure the water status in barley, and various QTLs for RWC on chromosomes 2H, 4H, 5H, 6H and 7H have been detected in different water conditions (Teulat et al, 2003;Fan, Shabala, Ma, Xu, & Zhou, 2015;Liu et al, 2015). In the current study, no QTLs controlling RWC were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed analyses on vrs1 mutants and their wild‐type backgrounds showed that VRS1 affects leaf width from as early as the P1 primordium stage, possibly by controlling cell proliferation (Thirulogachandar et al ). Interestingly, QTL analysis in a double haploid progeny detected a major QTL for flag leaf area, width and length in correspondence with the VRS1 locus (Liu et al ). As row‐type genes are also known to affect tillering (Liller et al ), understanding the pleiotropic effects of these genes on tiller number and leaf size is a prerequisite to optimize source‐sink relationships and improve yield.…”
Section: Genetics Of Barley Shoot Architecturementioning
confidence: 99%
“…QTLs associated with photosynthetic traits have rarely been reported in barley due to measurement procedures and the complicated, dynamic processes of these phenotypic traits. Liu et al [33] identified several QTLs located on chromosomes 2H, 3H and 7H associated with intercellular CO 2 concentration, transpiration rate and stomatal conductance from barley flag leaves on plants grown under normal conditions. QTLs for net photosynthetic rate, transpiration rate and stomatal conductance have also been found in rice [29].…”
Section: Discussionmentioning
confidence: 99%
“…QTLs for gas exchange and stomatal parameters under greenhouse conditions or different stresses have been identified in Arabidopsis [27], rice [8, 28, 29], sunflower [30], and faba bean [31]. In barley, QTLs associated with net photosynthetic rate have been detected under drought stress [32] and without stress [33], and QTLs for stomatal conductance [33] and stomatal density [34] have been identified in barley grown without stress. However, to the best of our knowledge, QTLs for stomatal traits, especially stomatal aperture and guard cell and subsidiary cell geometry under salinity stress, have not been reported in plants.…”
Section: Introductionmentioning
confidence: 99%